Odpowiedź:
Szczegółowe wyjaśnienie:
[tex]2^4=a\\a=16\\\\(\frac{1}{5})^5=b\\b=\frac{1}{5^5}\\\\16^{\frac{1}{4}}=c\\c=\sqrt[4]{16}=2\\\\5^{\frac{1}{2}}=d\\d=\sqrt{5}\\\\(\sqrt{3})^\frac{1}{2}}=e\\e=(3^{\frac{1}{3}})^{\frac{1}{2}}=3^{\frac{1}{3}*\frac{1}{2}}=3^{\frac{1}{6}}=\sqrt[6]{3}\\\\({\frac{2}{5}})^{-1}=f\\f=\frac{5}{2}=2\frac{1}{2}\\\\2^{-5}=g\\g=\frac{1}{2^5}=\frac{1}{32}\\\\4^2=h\\h=16\\\\10^{\sqrt{3}}=i\\\\10^{-0,5}=j[/tex]\
[tex]j=\frac{1}{10^{0,5}}=\frac{1}{10^{\frac{1}{2}}}=\frac{1}{\sqrt{10}}*\frac{\sqrt{10}}{\sqrt{10}}=\frac{\sqrt{10}}{10}\\\\10^2=k\\k=100\\\\10^{\frac{1}{3}}=l\\l=\sqrt[3]{10}[/tex]